Conflict in Pre-Hispanic Northwest Argentina: Implications Arising From Human Bone Trauma Patterns - Gheggi, María Soledad (2016)
The time span ranging from ca. 900 to 1450A.D. in the South-Central Andes has been traditionally posited as a period of social unrest, political disintegration and large-scale conflict due to, primarily, environmental causes. However, the osteological record of traumatic injuries in a sample of 223 adult and subadult crania from different areas of Northwest Argentina does not clearly correspond to the expected scenario of pervasive and formalized armed attacks. Cranial trauma prevalence in the sample is low (17.48%), and no statistically significant differences were met between the sexes. No differences were found when comparing trauma prevalence between settlements or regions, suggesting that location or function of the sites may not have influenced in trauma frequencies. This information more comfortably agrees with a scenario of conflict where several sources of violence may have caused the record of traumatic injuries (i.e. raids, ambushes, etc). These results serve to problematize how conflict is expected to be expressed in the archaeological record, especially in osseous human remains, what sources of violence may have generated the traumatic patterns observed and the intensity of conflict in this region in particular and in the pre-Hispanic Andes in general.